2018
DOI: 10.1002/ajh.25104
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myelomonocytic leukemia: 2018 update on diagnosis, risk stratification and management

Abstract: Hypomethylating agents such as 5-azacitidine and decitabine are commonly used, with overall response rates of ∼30%-40% and complete remission rates of ∼7%-17%; with no impact on mutational allele burdens. Allogeneic stem cell transplant is the only potentially curative option, but is associated with significant morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 117 publications
5
115
0
6
Order By: Relevance
“…10 Ever since, data with regards to HMA efficacy in CMML has been largely retrospective, with overall response rates (ORR) ranging from 40%-50% and true complete remission rates (CR) generally being <20%. 8 A recent prospective phase II study of DAC in CMML (n = 43) demonstrated a CR rate of 16%, with an ORR of 47%. 11 When analyzed by CMML specific subcategories, the response rates were even lower in MP-CMML; CR 14% (vs 21% in MD-CMML) and ORR 39% (vs 64% in MD-CMML).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 Ever since, data with regards to HMA efficacy in CMML has been largely retrospective, with overall response rates (ORR) ranging from 40%-50% and true complete remission rates (CR) generally being <20%. 8 A recent prospective phase II study of DAC in CMML (n = 43) demonstrated a CR rate of 16%, with an ORR of 47%. 11 When analyzed by CMML specific subcategories, the response rates were even lower in MP-CMML; CR 14% (vs 21% in MD-CMML) and ORR 39% (vs 64% in MD-CMML).…”
Section: Introductionmentioning
confidence: 98%
“…7 While allogeneic hematopoietic stem cell transplant (allogeneic-HCT) remains the only curative modality for CMML, it is not an option for the vast majority, as most patients are diagnosed in their 7 th decade of life and have limiting comorbidities. 8 Hypomethylating agents (HMA) such as 5-azacitidine (AZA) and decitabine (DAC), remain the only US FDA approved agents for the management of CMML, with approval of these agents based on the inclusion of small numbers of CMML patients in MDS-predominant clinical trials. The pivotal North American CALGB study (n = 191) only included 14 CMML patients; 7 being assigned to the AZA arm and 7 to the best supportive care (BSC) arm.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic myelomonocytic leukemia (CMML) is a myeloid neoplasm characterized by a pathologic accumulation of monocytic cells manifesting with coexisting signs of myeloproliferation and myelodysplasia and associated with an increased risk of transformation to secondary acute myeloid leukemia (AML). The overall incidence of CMML is estimated to be around four cases per 100 000 persons/y; it usually affects elderly patients with a median age at diagnosis of 75 years and a slight male predominance . Survival time is highly variable, ranging from 1 to >100 months.…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of CMML is estimated to be around four cases per 100 000 persons/y; it usually affects elderly patients with a median age at diagnosis of 75 years and a slight male predominance. 1 Survival time is highly variable, ranging from 1 to >100 months. High white blood cell count (WBC), anemia, splenomegaly, high lactate dehydrogenase level, thrombocytopenia, and lymphocytosis are associated with a poor prognosis 2 and are therefore included in a CMML-specific prognostic scoring system.…”
Section: Introductionmentioning
confidence: 99%
“…The cytogenetic risk was based on the comprehensive cytogenetic scoring system (CCSS) for MDS, on the ELN risk stratification for AML, and on the Spanish CMML-specific cytogenetic risk stratification for CMML, respectively. 21,[30][31][32] In summary, the standard operating procedures in our center recommended using 5-AZA as frontline therapy for patients with AML and high-risk MDS with an adverse karyotype in patients younger than 75 years old, with a good performance status (ECOG < 2), without severe comorbidities (the hematopoietic cell transplant comorbidity index (HCTI) <4). Those with the same characteristics but with lower risk cytogenetics were treated with 5-AZA as maintenance after induction chemotherapy.…”
Section: Treatment Protocolmentioning
confidence: 99%